Pengenaan Pajak Penghasilan Pengusaha E-Commerce Shopee Berdasarkan Peraturan Pemerintah No 23 Tahun 2018 - Isna Ardila; Zuraida Ulfa (CERED Indonesia Institute, 2022)
This study aims to analyze the compliance of e-commerce entrepreneurs regarding the imposition of income tax on online businesses based on Government Regulation no. 23 of 2018. This study uses a descriptive research approach, and from 110 populations or respondents used 15 Shopee e-commerce entrepreneurs spread across the city. Medan as the research sample obtained from purposive sampling technique. Data collection techniques were carried out using questionnaires and interviews. The results showed that the tax compliance of Shope e-commerce entrepreneurs in Medan City on Government Regulation no. 23 of 2018 is still classified as very low due to the lack of understanding of e-commerce entrepreneurs regarding Government Regulation no. 23 of 2018 causing non-compliance in carrying out the obligation to pay taxes.